Case Report: Aicardi-Goutières Syndrome and Singleton-Merten Syndrome Caused by a Gain-of-Function Mutation in IFIH1 - Xiao, Wei; Feng, Jie; Long, Hongyu; Xiao, Bo; Luo, Zhaohui H. (Frontiers in Genetics, 2021)
The IFIH gene encodes melanoma differentiation-associated gene 5 (MDA5) and has been associated with Aicardi-Goutières syndrome (AGS), Singleton-Merten syndrome (SMS), and other autoimmune diseases. The mechanisms responsible for how a functional change in a single gene can cause so many different phenotypes remain unknown. Moreover, there is significant controversy as to whether these distinct phenotypes represent the same disease continuum or mutation-specific disorders. Here, we describe the case of a patient with a novel c.1465G>T (p.Ala489Ser) mutation in the IFIH1 gene. The patient presented with spastic paraplegia, dystonia, psychomotor retardation, joint deformities, intracranial calcification, abnormal dentition, characteristic facial features, lymphadenopathy and autoimmunity. His phenotype appeared to represent an overlap of the phenotypes for AGS and SMS. The patient also experienced unexplained pancytopenia, suggesting that the hemic system may have been affected by a gain-of-function mutation in the IFIH1 gene. In summary, we provide further evidence that SMS and AGS exhibit the same disease spectrum following a gain-of-function mutation in the IFIH1 gene. Our data highlight the genetic heterogeneity of these conditions and expand our knowledge of differential phenotypes created by IFIH1 gain-of-function mutation.